Cryogenic Sulfuric Weathering and Challenges for Preserving Iron‐Rich Olivine on Cold and Icy Mars. Issue 1 (30th December 2022) - Yu, Xiao‐Wen; Zhao, Yu‐Yan Sara; Wu, Yanxue; Qi, Chao; Li, Dongdong; Lin, Honglei; Yang, Shiling; Liu, Jianzhong; Li, Xiongyao
Abstract: Iron‐rich olivine (Fe contents ≥20%) is widely distributed on Mars, but its dissolution rates, weathering products, and particularly Fe behavior under Mars‐relevant conditions are largely unconstrained. Here, we experimentally investigate the dissolution of synthetic Fe‐rich olivine (Fa29 to Fa100 ; grain size ∼53 μm) for a water‐limited cryogenic sulfuric weathering scenario at 233 K. Fayalite (Fa) and forsterite (Fo) in Fo‐dominant olivine dissolve simultaneously, whereas fayalite dissolution in Fa‐dominant olivine is hindered. Primary alteration products are Fe II ‐Mg‐sulfates and amorphous silica with minor ferric sulfates and gypsum. Freezing and acidic conditions enhance Fe mobility and subsequent Fe cycling on Mars. The lifetime of Fe‐rich olivine is two to three orders of magnitude shorter than that of Mg‐rich San Carlos olivine. The cryogenic sulfuric weathering scenario greatly challenges the survival of Fe‐rich olivine. Spatial and temporal restrictions for acid‐olivine interactions or insufficient sulfur supply relative to olivine are essential to preserving olivine throughout cold and icy ancient Mars. Plain Language Summary: Cryogenic sulfuric weathering is proposed for forming large‐scale layered sulfate deposits on Mars, such as Meridiani Planum and Valles Marineris. In particular, olivine dissolution is essential for producing these evaporative sulfate assemblages. Although qualitatively likely, how Fe‐rich olivine, widely distributed in Martian basaltic crusts, would respond to the cryogenic sulfuric weathering scenario is currently unknown. We synthesized Fe‐rich olivine samples (Fa29 ∼ Fa100 ) and investigated their dissolution processes and alteration products under sulfuric acidic conditions at 233 K. We found that forsterite and fayalite in Fo‐dominant olivine (Fa# ≤ 50) dissolve simultaneously, whereas the dissolution of fayalite in Fa‐dominant olivine (Fa# > 50) is hindered. Primary alteration products are Fe II ‐Mg‐sulfates and amorphous silica with minor ferric sulfates and gypsum. Freezing and acidic conditions enhance Fe mobility and subsequent Fe cycling on Mars. Fe‐rich olivine dissolves two to three orders of magnitude faster than Mg‐rich San Carlos olivine, and 0.1 mm Fe‐rich olivine grains can survive only 10s to 100s of years under H2 SO4 ‐233 K conditions. The cryogenic sulfuric weathering scenario greatly challenges the survival of Fe‐rich olivine. Thus, spatial and temporal restrictions for acid‐olivine interactions or insufficient sulfur supply relative to olivine are essential for preserving olivine throughout cold and icy ancient Mars. Key Points: Forsterite‐dominant olivine dissolves stoichiometrically, but the dissolution of fayalite in Fa‐dominant olivine is hindered Fe‐rich olivine alteration primarily produces Fe II ‐Mg‐sulfates and amorphous silica, with minor ferric sulfates and gypsum Fe‐rich olivine lasts 10s to 100s of years and restricting acid‐olivine interactions is essential for preserving olivine on cold and icy Mars